New Evidence on Price Anomalies in Sequential Auctions : Used Cars in New Jersey - Yaron Raviv (Claremont McKenna College, Department of Economics, 2004)
In this paper the sequence of winning bids in the public auction of used cars in New Jersey is examined for the presence of price anomalies. Unlike many studies of heterogeneous objects where the effect of the order of sale on the price may not be credibly identified, the effect of the order is identified here because the items are randomly selected for sale. In a further contrast to many other studies, these data indicate that the prices tend to increase as the auction proceeds. The data also indicate that once several items have been sold, there is no change in the bidding behavior or further increase in prices.
Keywords: C81; D44; C93; 330; Auction; Declining Price Anomaly; Auktion; Auktionstheorie; Preis; Gebrauchtfahrzeug; New Jersey